Roles for the RNA-Binding Protein Caper in Reproductive Output in Drosophila melanogaster - Erika J. Tixtha; Meg K. Super; M. Brandon Titus; Jeremy M. Bono; Eugenia C. Olesnicky (Journal of Developmental Biology, 2022)
RNA binding proteins (RBPs) play a fundamental role in the post-transcriptional regulation of gene expression within the germline and nervous system. This is underscored by the prevalence of mutations within RBP-encoding genes being implicated in infertility and neurological disease. We previously described roles for the highly conserved RBP Caper in neurite morphogenesis in the Drosophila larval peripheral system and in locomotor behavior. However, caper function has not been investigated outside the nervous system, although it is widely expressed in many different tissue types during embryogenesis. Here, we describe novel roles for Caper in fertility and mating behavior. We find that Caper is expressed in ovarian follicles throughout oogenesis but is dispensable for proper patterning of the egg chamber. Additionally, reduced caper function, through either a genetic lesion or RNA interference-mediated knockdown of caper in the female germline, results in females laying significantly fewer eggs than their control counterparts. Moreover, this phenotype is exacerbated with age. caper dysfunction also results in partial embryonic and larval lethality. Given that caper is highly conserved across metazoa, these findings may also be relevant to vertebrates.